PENERAPAN SISTEM INFORMASI LAYANAN PUBLIK DI DESA SUMBERDADI KECAMATAN TANALILI KABUPATEN LUWU UTARA - Nirsal, Nirsal; Jumardi, Andi; Syafriadi, Syafriadi; Nurfalaq, Aryadi; Putri, Iin Karmila (Universitas Mataram, 2024)
Sustainable Development Goals or usually abbreviated as SDGs is a sustainable development role that is included in the village development priority program. The Village Information System (SID) is part of an e-government system owned by the village, where this system is a system that will assist village officials in resolving village administration problems such as managing correspondence, as well as managing village population data which includes native population data. and immigrant population data. Sumberdadi Village is a village in the Tanalili District, North Luwu Regency. The main objective of this PKM activity is that the implementing team will implement information system technology that can be utilized by Sumberdadi Village officials in public services and archiving various documents owned, in addition to providing reinforcement to Sumberdadi village officials regarding the use of information technology that can be used in governance. village office. The method used in implementing PKM includes several stages, namely (1) Socialization and Interview Preparation Stages (2) Technology Implementation and Application Stages (3) Mentoring Stages (4) Evaluation Stages. The results of the outreach activities and workshops carried out by the implementing team increased the participants' knowledge and increased the soft skills of Sumberdadi village officials in terms of knowledge about the basic concept of smart villages, the use of village administration structuring applications and the use of the SIPEDES Sumberdadi application. The participant response to this PKM activity was very positive and beneficial for the participants. The activities carried out at each stage can increase the participants' insight and knowledge.